Antihypertensive efficacy and safety of benidipine and its effects on cardiac structure and function in elderly Chinese patients with mild to moderate hypertension: an open-label, long-term study - Qi, Weilin; Fan, Weihu (Arzneimittelforschung, 2011)
Benidipine (CAS 91599-74-5) has been reported as an effective antihypertensive treatment and its cardioprotective effects have been shown in several basic and clinical studies. However, the long-term efficacy and safety of benidipine remain unknown in elderly Chinese patient with hypertension. In this prospective, multicenter, open-label clinical trial, 152 eligible patients aged 60 to 75 years with mild to moderate essential hypertension (sitting systolic blood pressure (BP) ≥ 140 mmHg and/or sitting diastolic BP ≥ 90 mmHg) entered a 52-week study. All patients initially received benidipine 2–4 mg once a day, followed by titration to benidipine 8 mg/day to achieve the target BP (< 140/90 mmHg in non-diabetics and < 130/80 mmHg in diabetics). Add-on hydrochlorothiazide (CAS 58-93-5) and/or metoprolol tartaric acid (CAS 3750-58-6) were permitted during the study. Overall, 132 patients completed the 52-week treatment with benidipine as monotherapy or combination therapy. It showed that the regimen based on benidipine provided an obvious mean trough BP reduction of 13.8 ± 12.4/8.3 ± 9.2 mmHg (p < 0.001), and 62.5% of patients reached the target BP. In patients with left ventricular hypertrophy, the left ventricular mass index significantly decreased from 147.1 ± 27.6 g/m2 at baseline to 136.0 ± 17.5g/m2 at 52 weeks (p = 0.036). Clinical adverse events (AEs) were found in 15.1% of all patients, and six patients discontinued the treatment due to drug-related AEs during the entire trial. Patients' compliance was an average of 98.7%. Benidipine, with a favorable tolerability profile, provides a long-term antihypertensive effect and potential benefit for the heart in elderly patients with mild to moderate hypertensive, suggesting that it is suitable for elderly patients with hypertension.
Keywords: Benidipine; Calcium channel antagonist; CAS 91599-74-5; Elderly patients; Hypertension; Left ventricular hypertrophy